(untitled) (Malay Literature, 2017)
Iltizam is an anthology of poetry produced by Zubir Osman in 2015, in his effort to deliver poems with the element of dakwah or propagation of Islam and to showcase local wisdom, in particular that of the Bajau ethnic group in Sabah. This article focuses on 59 selected poems in the anthology that contain the elements of dakwah and local wisdom. The discussion in this article focuses on the dakwah element which is portrayed in and linked to the culture, way of life and nature of the Bajau people. The dakwah approach is the principle contained in the Malay Methodology Theory which has been used to explore the dakwah aspect while the Utilitarian Approach is used to examine local wisdom characteristics which reflect the heritage and identity of the Bajaus in Sabah. This analysis of Iltizam selected poems finds that the poems with the Islamic element not only involve the writer’s imaginative capability and creativity but they also become effective vehicles for dissemination to the public. It can be concluded that Iltizam presents the dakwah element and local wisdom of the Bajau people through the poetic verses as a manifestation of the world view and beliefs of its society. Keywords: Bajau ethnic group, Iltizam, poetry with dakwah element, local wisdom, Dakwah Approach, Malay Methodology Theory